The Relationship Between Interpersonal Communication and Social Culture in Stunting Prevention at Marusu Health Center - Yudha Pamungkas; Yusriani Yusriani; Abdul Gafur; Andi Asrina; Fairus Prihatin Idris; Muh. Khidri Alwi (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
Stunting remains one of Indonesia’s major chronic nutritional problems and poses a serious threat to human resource development, particularly in vulnerable regions such as Maros Regency. Stunting reflects long-term nutritional deficiencies during the critical period of the first 1,000 days of life and is associated with adverse consequences on physical growth, cognitive development, health status, and future productivity. Data indicate that the prevalence of stunting in the working area of the Marusu Health Center increased to 4.1% in 2024, highlighting the need for more effective preventive strategies that address not only biological and nutritional factors but also behavioral and communicative aspects. This study aimed to analyze the relationship between interpersonal communication and stunting prevention and management behaviors at the Marusu Health Center, Maros Regency. An analytical observational design with a cross-sectional approach was employed. The study population consisted of 284 mothers with stunted children in the Marusu Health Center area. Based on sampling criteria and data collection during the study period, a total of 96 respondents were included in the final analysis using accidental sampling. Primary data were collected through face-to-face interviews using structured questionnaires, while secondary data were obtained from the Marusu Health Center and the local Health Office. Data analysis was conducted using Chi-Square tests and multivariate logistic regression to identify significant associations between variables. The results showed that interpersonal communication was significantly associated with awareness, motivation, intention, and preventive practices related to stunting prevention. However, no significant relationship was found between interpersonal communication and sociocultural factors (p = 0.629). These findings indicate that effective interpersonal communication plays a crucial role in shaping preventive behaviors, even when sociocultural influences remain unchanged. Strengthening communication competencies among health workers and Posyandu (community health post) cadres, as well as implementing family-based counseling programs, is therefore essential. Future studies are recommended to expand the research area, increase the number of respondents, and apply longitudinal approaches to better understand the long-term effects of communication-based stunting prevention interventions.